Modeling of quality characteristics of the surface layer hardened by free-moving indenters under rotating electromagnetic field - Valery A. Lebedev; Anatoly A. Kochubey; Irina V. Chumak (Advanced Engineering Research)
It is shown that the magnetodynamic treatment implemented under the conditions of a rotating electromagnetic field is a kind of the dynamic methods of hardening free-moving indenters by the convection flows. It is proposed to use analytic dependences obtained by the approximation of the test data of effect of the surface plastic deformation (SPD) dynamic methods on the component hardened layer quality to evaluate quality parameters of the surface layer formed under the magnetodynamic processing. The resulting expression describing the experimentally established fact that the main contribution to the formation of the quality parameters of the hardened layer is made by the initial continuous coating of the treated surface with plastic prints is obtained. An analytical functional model establishing the surface layer quality parameters behavior depending on the multiplicity of covering the surface by the shock-pulse impact of the free-moving indenters is proposed. A comparative analysis of the experimental data obtained in the process of the magneto-dynamic processing with the calculated ones shows the applicability of the proposed models for predicting quality parameters of the hardened surface layer.